Relationship and production: the social organization of export agriculture in the province of Limon, Costa Rica, 1920-1960 - Putnam W., Lara Elizabeth (Revista de historia., 2001)
The author describes the imgrations patterns which shaped the demographic profile of the Caribbean lowlands of Costa Rica in the first half of the twentieth century, and goes on to analyze gender roles and kinship forms among residents of the zone, and reproductive labor there.